Pengaruh Reputasi Kap, Audit Tenure, Ukuran Perusahaan, Dan Rotasi Auditor Terhadap Kualitas Audit - Winda Winda; Imam Hadiwibowo (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
The quality of an audit report on a financial statement is very important for shareholders or other third parties in making decisions. This study aims to examine the effect of hood reputation, audit tenure, company size, and auditor rotation on the audit quality of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The data used in this study were obtained from the Annual Publication Auditor Report for Manufacturing Companies for the period 2017-2021. The population of this study is 47 mining sector companies listed on the Indonesian Stock Exchange using a sample during the year under study. The analytical technique used in this study is logistic regression which aims to obtain a comprehensive picture of the relationship between variables. The analytical method used in this study consisted of descriptive statistical analysis, logistic regression analysis, overall fit model test, Nagelkerke's r square, regression model feasibility and research hypothesis testing. The results of the study partially show that the reputation of KAP has a negative effect on audit quality. Audit tenure has no effect on audit quality. Firm size has no effect on audit quality. Auditor rotation has a positive effect on audit quality. Meanwhile, simultaneously reputation, audit tenure, company size, and auditor rotation together have a significant influence on audit quality.